Point-of-care ultrasound for tuberculosis management in Sub-Saharan Africa-a balanced SWOT analysis - Véronique Suttels; Jacques Daniel Du Toit; Arnauld Attannon Fiogbé; Ablo Prudence Wachinou; Brice Guendehou; Frédéric Alovokpinhou; Péricles Toukoui; Aboudou Rassisou Hada; Fadyl Sefou; Prudence Vinasse; Ginette Makpemikpa; Diane Capo-Chichi; et al. (My University, 2022)
Point-of-care ultrasound (POCUS) is an increasingly accessible skill, allowing for the decentralization of its use to nonspecialist healthcare workers to guide routine clinical decision-making. The advent of ultrasound-on-a-chip has transformed the technology into a portable mobile health device. Because of its high sensitivity to detect small consolidations, pleural effusions, and subpleural nodules, POCUS has recently been proposed as a sputum-free likely triage tool for tuberculosis (TB). To make an objective assessment of the potential and limitations of POCUS in routine TB management, we present a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis based on a review of the relevant literature and focusing on Sub-Saharan Africa (SSA). We identified numerous strengths and opportunities of POCUS for TB management, e.g., accessible, affordable, easy to use and maintain, expedited diagnosis, extrapulmonary TB detection, safer pleural/pericardial puncture, use in children/pregnant women/people living with HIV, targeted screening of TB contacts, monitoring TB sequelae, and creating artificial intelligence decision support. Weaknesses and external threats such as operator dependency, lack of visualization of central lung pathology, poor specificity, lack of impact assessments and data from SSA must be taken into consideration to ensure that the potential of the technology can be fully realized in research as in practice.
Keywords: Point-of-care ultrasound; Sub-Saharan Africa; Tuberculosis